B-arrestin-2 Signaling Is Important to Preserve Cardiac Function During Aging - Capote, Andrielle E.; Batra, Ashley; Warren, Chad M.; Chowdhury, Shamim A. K.; Wolska, Beata M.; Solaro, R. John; Rosas, Paola C. (Frontiers in Physiology, 2021)
Experiments reported here tested the hypothesis that β-arrestin-2 is an important element in the preservation of cardiac function during aging. We tested this hypothesis by aging β-arrestin-2 knock-out (KO) mice, and wild-type equivalent (WT) to 12-16 months. We developed the rationale for these experiments on the basis that angiotensin II (ang II) signaling at ang II receptor type 1 (AT1R), which is a G-protein coupled receptor (GPCR) that promotes both G-protein signaling as well as β-arrestin-2 signaling. β-arrestin-2 participates in GPCR desensitization, internalization, but also acts a scaffold for adaptive signal transduction that may occur independently or in parallel to G-protein signaling. We have previously reported that biased ligands acting at the AT1R promote β-arrestin-2 signaling increasing cardiac contractility and reducing maladaptations in a mouse model of dilated cardiomyopathy. Although there is evidence that ang II induces maladaptive senescence in the cardiovascular system, a role for β-arrestin-2 signaling has not been studied in aging. By echocardiography we found that compared to controls aged KO mice exhibited enlarged left atria and left ventricular diameters as well as depressed contractility parameters with preserved ejection fraction. Aged KO also exhibited depressed relaxation parameters when compared to WT controls at the same age. Moreover, cardiac dysfunction in aged KO mice was correlated with alterations in the phosphorylation of myofilament proteins, such as cardiac myosin binding protein-C (cMyBP-C), and myosin regulatory light chain (RLC). Our evidence provides novel insights into a role for β-arrestin-2 as an important signaling mechanism that preserves cardiac function during aging.